In Silico Approach for DNA Barcoding using Phylogenetic Analysis of Coelogyne spp. based on the matK, rpoC1, rbcL and nrDNA Markers - Pratiwi, Apriliana; Kinasih, Anggiresti; Meidianing, Maura Indria; Kurniawan, Febri Yuda; Semiarti, Endang (Journal of Tropical Biodiversity and Biotechnology, 2023)
In silico biology is considered as an effective and applicable approach to initiate various research, such as biodiversity taxonomical conservation. Phylogenetic analysis using in silico taxonomy method for orchid species can provide data on genetic diversity and evolutionary relationships. One particular method that can be used to evaluate specific targets of gene loci in the taxonomic study is DNA barcoding. This research was conducted to determine the specific target locus gene using matK, rbcL, rpoC1, and nrDNA markers for DNA barcoding of the Coelogyne genus with in silico approach using phylogenetic analysis. All marker sequences were collected from the NCBI website and analysed using several softwares and methods, namely Clustal X for sample sequence alignment and MEGA 11 for phylogenetic tree construction and analysis. The results showed that the gene locus in Coelogyne recommended was the nrDNA gene locus. Phylogenetic analysis revealed that the use of the nrDNA gene locus was able to separate 17 Coelogyne species with two outgroup species, namely Cymbidium and Vanilla, then followed with ribulose-1,5-bisphosphate carboxylase/oxygenase large subunit (rbcL) while the other gene loci, namely maturase K (matK) and polymerase beta' subunit (rpoC1) provided a visual phylogenetic tree in which the two outgroup species entered into the same clade as the Coelogyne species. Thus, the results of this study can be used as a reference to support the Coelogyne breeding and conservation program.